A 46-year-Oldman with Gynaecomastia and Cirrhosis Hepatis Child Plug A. A case Report - Dian Rosa Lubis, Syarifah; Melati Silvani (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background: Gynecomastia is defined as the presence of excessive breast tissue in males, which can appear unilateral or bilateral. Bilateral prepubertal gynecomastia in the absence of endocrine abnormalities is extremely rare, with only a few cases in literature. Case Presentation: A 46-year-old man presented with a 2 years history of bilateral breast enlargement and pain. There is heartburn, shrinking testicles, and decreased sexual drive. Vital examination showed normal. BMI : 24. 0 kg/m². Head dan neck: normal. On the chest both breasts are enlarged as avocados, palpable time around areola, chewy contingency, press pain, galactorrhea negative. Lung and cast are normal. In the abdominal: hepar, lien and renal are not palpable, and ascites are not found. There is an atrophy of testicles. Previous history of hepatic cirrhosis with Esophageal Varicose Veins caused by Hepatitis B. Laboratory examination Estradiol 98.71 pg/mL (range: <62), Testosterone: 8.66 ng/mL (range: 3.0-10.6), LH5.53 mlU/mL, FSH 6.49 mlU/mL, Prolactin 5.08 ng/mL; Total T4 5.57 ng/dL , TSH 1.84 μIU/mL. SGOT U/L 53, SGPT 71 U/L, Hepatitis B (+), HBsAg Reactive S/CO 414.46; HBeAg: Non Reactive, HBV DNA Undetectable and Albumin 3.6 g/dL. Fibroscan: Cirrhosis Hepatis. Abdominal ultrasound: Cirrhosis Hepatis. Gastroscopy: Esophageal Varicose Veins (F1, LI, CB) + Pan Gastropathy. Conclusion: Reportedly A 46-year-old man presented with gynaecomastia bilateral with Cirrhosis Hepatis Child Plug A, given conservative treatment with tamoxiphen for 1 month